Oxytocin increases eye-gaze towards novel social and non-social stimuli - Eckstein, Monika; Ditzen, Beate (Social neuroscience, 2018)
Research on oxytocin (OT) has revealed a substantial involvement of this neuropeptide in social cognition processes and attachment behavior.The rationale of the present project was to decipher the differential role of OT in basic social cognition processes towards non-erotic attachment stimuli vs. reproduction-related stimuli in human subjects.In a randomized double-blind repeated-measures cross-over design, N = 82 participants were investigated twice and received either intranasal OT or placebo at the first assessment followed by placebo or OT at second assessment. Participants were presented with standardized pictures of parent-child dyads, romantic couples engaging in non-erotic or explicit sexual activities, and non-social pictures while we assessed pupil dilation and eye focus on specific pre-defined areas of interest. Multilevel analyses suggest that during the initial presentation, OT increased pupil dilation towards all categories of stimuli and led the eye focus towards the eyes and body regions, followed by a strong decrease in pupil dilation and fixations at the second session.These carry-over effects indicate that hormonal treatment at an initial contact to social stimuli can determine how these stimuli are processed later. These results might have implications for OT as a treatment in interventions with repeated exposure to social material.